Shifting the affective narrative: atmospheres as solicitations to alter situational emotion scripts - Vespermann, Daniel (Philosophical psychology, 2024)
Over the past decade, the notion of affective affordances has gained some prominence, particularly in the context of 4E approaches to affectivity. One example of affective affordances, mostly mentioned in passing in 4E approaches to affectivity, are atmospheres. Notoriously difficult to pin down in general, it has so far also remained unclear what distinguishes atmospheres from other affective affordances and whether they are a distinctive type of solicitations. Intuitively, the atmosphere of a situation implies an affect-regulatory profile different to what and how single objects solicit. Notably, as affective frames of sociocultural delineated situations they are relevant for coordinating social interactions and modulate personal concerns pertaining to a given situation. In accordance with paradigm cases of experiencing atmospheres, I will claim that they make salient how one is affectively disposed toward situation-specific feeling norms. I will clarify this claim by drawing on the concepts of social and emotion scripts as they have been developed in cognitive psychology and psychology of emotions. Atmospheres will thus be understood as solicitations to change situational emotion scripts. In this way, they represent a distinct avenue for changing fields of affordances over time, based on personal concerns for social and cultural belonging. Conversely, this account sheds light on the affective underpinnings of the perception of social norms.
Gesehen am 15.11.2024